(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2019)
The aim of this paper is to study the effect of couple stress fluid on the static performance of an offset journal bearing. To find the pressure profile the Reynolds equation in non-dimensional form is solved using finite difference method. The static characteristics i.e. load carrying capacity, attitude angle and Sommerfeld number are determined and compared with Newtonian fluid. It was found that with the increase in couple stress parameter the load carrying capacity and attitude angle are enhanced and sommerfeld number is decreased. Effect of couple stress parameter on pressure profile is also carried out which shows that maximum increases with couple stress parameter.